Uplink User Capacity in a 2 tier CDMA Network in the Presence of Degenerate Users - Yahya, Norashikin; Kishore, Shalinee (2006)
This paper examines the uplink user capacity in a CDMA system composed of a macrocell with embedded “hotspot” microcell, where both cells use the same frequency channel. Analytical methods are presented here to quantify cross-tier interference (CTI) due to degenerate users. Simulation result verifies the analysis of CTI in the case if there is only one degenerate user. Also presented here is the analysis for computing user capacity in the presence of degenerate users, which account for propagation loss, multiple access interference, power control, and random locations of user terminal considering path gain tier selection method. These results point to reduction in capacity performance when degenerate users present in the microcell.